2020
DOI: 10.3389/fphys.2020.501383
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Physiological Rhythms Persist Following Cessation of Cigarette Smoke Exposure in Mice

Abstract: Background: Physiological rhythms in mammals are essential for maintaining health, whereas disruptions may cause or exacerbate disease pathogenesis. As such, our objective was to characterize how cigarette smoke exposure affects physiological rhythms of otherwise healthy mice using telemetry and cosinor analysis. Methods: Female BALB/c mice were implanted with telemetry devices to measure body temperature, heart rate, systolic blood pressure (SBP), and activity. Following baseline measurements, mice were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…While studies have demonstrated that cannabis smoke increases locomotion in rats [ 40 ], our model appears to have the opposite effect, potentially due to the opposing effects of prolonged time in the smoke-filled exposure chamber. TPM in the chamber was seen to be at similar levels to those seen in tobacco smoke studies using the same system [ 25 , 39 ], which may also contribute to the tobacco smoke-like behavioural phenotype we observed. While TPM alone contributes to lung inflammation [ 41 , 42 ], cannabis smoke contains a myriad of other chemical components, cannabinoids, and reactive oxygen species, which can alter cellular and immunological functions.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…While studies have demonstrated that cannabis smoke increases locomotion in rats [ 40 ], our model appears to have the opposite effect, potentially due to the opposing effects of prolonged time in the smoke-filled exposure chamber. TPM in the chamber was seen to be at similar levels to those seen in tobacco smoke studies using the same system [ 25 , 39 ], which may also contribute to the tobacco smoke-like behavioural phenotype we observed. While TPM alone contributes to lung inflammation [ 41 , 42 ], cannabis smoke contains a myriad of other chemical components, cannabinoids, and reactive oxygen species, which can alter cellular and immunological functions.…”
Section: Discussionsupporting
confidence: 77%
“…Our cannabis smoke-exposure model was effective at delivering cannabis smoke to mice. Within the exposure chamber, mice displayed common symptoms of smoke exposure seen in our previous tobacco studies but tolerated smoke exposure well [ 25 , 39 ]. While studies have demonstrated that cannabis smoke increases locomotion in rats [ 40 ], our model appears to have the opposite effect, potentially due to the opposing effects of prolonged time in the smoke-filled exposure chamber.…”
Section: Discussionmentioning
confidence: 99%
“…While studies have demonstrated that cannabis smoke increases locomotion in rats 37 , our model appears to have the opposite effect, potentially due to the opposing effects of prolonged time in the smoke-filled exposure chamber. TPM in the chamber was seen to be at similar levels to those seen in tobacco smoke studies using the same system 25,36 , which may also contribute to the tobacco smoke-like behavioural phenotype we observed. In our post-exposure analysis, we found elevated levels of COHb, THC, and carboxy-THC across the sexes that decreased 60 minutes post exposure (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Our cannabis smoke exposure model was effective at delivering cannabis smoke to mice. Within the exposure chamber, mice displayed common symptoms of smoke exposure seen in our previous tobacco studies but tolerated smoke exposure well 25,36 . While studies have demonstrated that cannabis smoke increases locomotion in rats 37 , our model appears to have the opposite effect, potentially due to the opposing effects of prolonged time in the smoke-filled exposure chamber.…”
Section: Discussionmentioning
confidence: 82%
“…Knockout mice for Rev-erbα, an important circadian clock component, showed increased susceptibility to inflammation after exposure to cigarette smoke-derived PM ( 228 ). Natural physiological rhythms of mice did not recover even 4 weeks after cessation of smoke exposure ( 239 ). Also, altered methylation of the Clock gene was found in blood cells of free-living birds in dependence of PM10 exposure ( 202 ).…”
Section: Connection Of Air Pollution Circadian Clock Dysregulation An...mentioning
confidence: 99%